FROM PRACTICE TO PERFECTION: A SURGICAL HAND SCRUBBING AUDIT IN INTERNEE TRAINING (The Research of Medical Science Review, 2025)
Background: Proper surgical hand scrubbing is essential for maintaining asepsis and preventing surgical site infections (SSIs), which remain a major challenge, particularly in developing countries. Although surgeons understand its importance, many fail to follow the complete protocol, compromising patient safety and increasing the risk of hospital-acquired infections due to inadequate sterilization practices.Methods: A prospective audit assessed surgical hand scrubbing compliance among 25 trainees, including residents and house surgeons. Baseline data were gathered in cycle one, followed by interventions—video demos, hands-on training, and feedback—before cycle two. WHO standard criteria guided pre- and post-intervention assessments. Data was checklist-based, analyzed quantitatively for compliance rates, and qualitatively to explore adherence barriers.Results: In the first audit cycle, overall compliance was 86.25%, which improved to 93.25% after targeted interventions. Significant improvements were observed in previously weak steps, with gains between 30% and 45%. Strong initial compliance steps were maintained. The findings highlight that structured training, feedback, and continuous auditing can significantly enhance adherence to surgical hand hygiene protocols.